The Influence of Good Corporate Governence Principles, Transformational Leadership, and Tri Hita Karana Culture on Profitability - Ayu Sugandha; I Gusti Ayu Made Asri Dwija Putri (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
The purpose of the study is to empirically test the effect of transparancy, accountability, responsibility, independency, fairness, transformational leadership, and Tri Hita Karana culture on profitability. The population used is LPDs in Denpasar city. Sampling was done by using saturation sampling methods. The data collection was done by survey method by distribution of questionnaires adn LPDs finansial reports. The data analysis technique used was multiple linear regression analysis. The result showes that transparency, accountability, responsibility, independency, fairness, and Tri Hita Karana culture have a positive effect on profitability LPDs. Meanwhile, transformational leadership has no effect on profitability.